Cestodes of the blue shark, Prionace glauca (Linnaeus 1758), (Carcharhiniformes: Carcharhinidae), off the west coast of Baja California Sur, Mexico - Méndez, Oscar; Galván-Magaña, Felipe (Zootaxa, 2016)
The cestode species recovered from the spiral intestines of 27 blue sharks (Prionace glauca) (Linnaeus, 1758) are reported from the western coast of Baja California Sur (BCS). The sampling was undertaken on a monthly basis from January 2003 to January 2004. The helminthological examination indicated the presence of four species of cestodes: Platybothrium auriculatum Yamaguti, 1952; Prosobothrium japonicum Yamaguti, 1934; Anthobothrium caseyi (Yamaguti, 1934) Ruhnke & Caira, 2009; and Paraorygmatobothrium prionacis (Yamaguti, 1934) Ruhnke, 1994. Of all the 27 sharks examined, 88.8% were infected with at least one cestode species. The most frequent species was P. auriculatum infecting 85% of the spiral intestines examined. In contrast the species with the highest mean intensity was P. prionacis (80.4 200). The species richness of cestodes in P. glauca is very similar in other regions of the world despite its wide distribution; however, this richness is low compared with other species of sharks within the same family. The feeding and host-specific are important factors that influence the parameters of infection of cestodes in this shark. On the west coast of BCS, Prionace glauca feeds mainly on red crab Pleuroncodes planipes Stimpson, 1860; squids Gonatus californiensis Young, 1972, Ancistrocheirus lesueurii (D’Orbigny, 1842), Haliphron atlanticus Steenstrup, 1861, and low proportion of fish teleosts as Merluccius productus (Ayres, 1855), Sardinops sp. Hubbs, 1929 and Scomber japonicus Houttuyn, 1872. We speculate that these prey could be involved as the second intermediate hosts of these cestodes, as in other members of these genera, although the life cycles of none are known.